Description of the third instar of Macraspis clavata (Olivier, 1789 (Coleoptera: Scarabaeidae: Rutelinae) - Medeiros, Rone A.f.; Frazão, Carlos A. V.; Grossi, Paschoal C.; Fuhrmann, Juares (Zootaxa, 2019)
The third instar of Macraspis clavata (Olivier, 1789), collected in Rio Grande do Sul, Brazil, is described. Illustrations, comments on the natural history, and a key to third instar of Macraspis are also added.